2021
DOI: 10.1148/radiol.2021210972
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic Interstitial Lung Abnormalities at 1-year Follow-up CT after Severe COVID-19

Abstract: In Press" papers have undergone full peer review and have been accepted for publication in Radiology. This article will undergo copyediting, layout, and proof review before it is published in its final version. Please note that during production of the final copyedited article, errors may be discovered which could affect the content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 7 publications
5
83
0
2
Order By: Relevance
“…and "irregular lines" with small patient cohorts recovering from severe disease 18,21 and the majority with relatively short-term (up to 6 months) follow-up. [22][23][24][25] Studies evaluating serial radiologic changes after COVID-19 are lacking. Therefore, the aim of the present study was to critically review chest CT abnormalities in COVID-19 survivors at up to 1-year follow-up in concert with symptomatology and indices of functional impairment, identify associations with inpatient characteristics, and evaluate serial radiologic findings.…”
Section: N P R E S Smentioning
confidence: 99%
“…and "irregular lines" with small patient cohorts recovering from severe disease 18,21 and the majority with relatively short-term (up to 6 months) follow-up. [22][23][24][25] Studies evaluating serial radiologic changes after COVID-19 are lacking. Therefore, the aim of the present study was to critically review chest CT abnormalities in COVID-19 survivors at up to 1-year follow-up in concert with symptomatology and indices of functional impairment, identify associations with inpatient characteristics, and evaluate serial radiologic findings.…”
Section: N P R E S Smentioning
confidence: 99%
“…However, a 1-year follow-up study on patients recovered from 2003 SARS showed that one-third of the patients had persistent pulmonary function impairment, and poorer health, in general, than the healthy population (9). So far, there are few follow-up studies over 1 year assessing the sequelae in the patients recovered from COVID-19 infection (10)(11)(12)(13). Furthermore, the studies on multi-system assessment of long-term consequences in COVID-19 survivors are limited.…”
Section: Introductionmentioning
confidence: 99%
“…A chest CT is significant in the assessment of lung lesions caused by COVID-19 [17,18]. A CT is widely used for admission screening, discharge assessment, and followup of COVID-19 patients [7,[19][20][21]. Therefore, our radiomic models based on admission and discharge chest CTs of COVID-19 survivors can be well validated.…”
Section: Discussionmentioning
confidence: 99%